2013
DOI: 10.1016/j.juro.2012.09.088
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Decompression is Associated with Decreased Mortality in Patients with Sepsis and Ureteral Calculi

Abstract: Absent surgical decompression is associated with higher odds of mortality in patients with sepsis and ureteral calculi. Further research to determine predictors of surgical decompression is necessary to ensure that all patients have access to this life saving therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 13 publications
1
57
0
2
Order By: Relevance
“…Therefore, nephrostomy was used much more often in our study. A delay in renal decompression or omitting it completely will increase the rate of sepsis and mortality [2,3,4,11,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nephrostomy was used much more often in our study. A delay in renal decompression or omitting it completely will increase the rate of sepsis and mortality [2,3,4,11,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Obstrükte sistemin tedavisi klasik olarak o sistemin drene; yani dekomprese edilmesidir. Üreter taşına bağlı ürosepsis tablosu ile hastaneye başvuruların incelendiği bir çalışmada toplam 1712 hasta retrospektif olarak değerlendirilmiş, cerrahi dekompresyon yapılmayan hastaların hastanede medikal tedavi altına alın-dıkları dönemde 2 kat daha fazla ölüm riski taşıdıkları gös-terilmiştir (21). Amerika Birleşik Devletleri'nde yapılan bu çalışmada bu hastaların %25'ine herhangi bir dekompresyon yöntemi uygulanmamıştır.…”
Section: üReteroskopi (Urs)unclassified
“…Rahman et al [4] reported that about two-thirds of OPN patients was accompanied by the presence of urinary stone. Other studies have reported that patients with a history of previous ureteral stone accompanied by sepsis had a mortality rate as high as 19%, if appropriate ureteral decompression were not performed [5]. Furthermore, if decompressive procedure was delayed due to the so-called "weekend effect," the mortality rate could be at risk of being elevated [6].…”
Section: Introductionmentioning
confidence: 99%